Effect of season and SNPs of HSP90 and HSP70 genes on the biochemical traits in Indian sheep (Ovis aries) breeds - SINGH, SANJEEV; SINGH, K M; GANGULY, INDRAJIT (The Indian Journal of Animal Sciences, 2020)
Heat shock proteins (HSPs) are evolutionary conserved family of proteins produced by living cells in response to various biological stresses, including heat shock. Heat stress affects the productivity of the livestock species, which causes severe economic losses to the animal keepers. The present study was undertaken to establish reference baseline values for thyroid (T3 and T4) and adrenal gland (cortisol) hormones in four indigenous sheep breeds (Chokla, Marwari, Magra and Madras Red). The effect of the seasons and genotypes of the HSP90 and HSP70 genes on the functions of the thyroid gland as well as cortisol levels were examined in plasma samples of these sheep breeds. A total of 80 plasma samples (10 animals per breed for the summer and winter season) were analyzed. The least square analysis revealed significant seasonal effect on Triiodothyronine (T3) and Thyroxine (T4). Significantly higher T3 and T4 levels were observed in the winter with a low temperature humidity index (THI) than in summer with high THI. Cortisol was non-significantly higher in the summer than in winter season. Overall, the influence of the breeds on these three parameters was non-significant. Genotypes of SNP1 (HSP90 gene) and SNP2 (HSP70 gene) had significant effect on T3 level. These SNP markers may be useful for identifying animals that are more adaptable to heat stress following a thorough association analysis over a large sample size.